IMPACT OF DIRECTIVE LEADERSHIP, ENVIRONTMENT, AND WORK MOTIVATION ON HOSPITAL EMPLOYEE PERFORMANCE - Tias Muji Hartono; Meiske Claudia (Adisam Publisher, 2025)
This research analyzes the influence of directive leadership, work environment, and work motivation on employee performance at Paradise Maternity Hospital, Tanah Bumbu Regency. The method used is quantitative with a type of causal research. The research population was 72 employees of Paradise Maternity Hospital using a saturated sampling technique. Data collection was carried out through questionnaires and documentation. Data analysis uses multiple linear regression after fulfilling the classical assumption test. The research results show that directive leadership, work environment, and work motivation positively and significantly affect employee performance. Effective directive leadership with clear direction, a comfortable and conducive work environment, and high employee work motivation can improve employee performance in quality, quantity, timeliness, effectiveness, and independence. It is recommended that management improve directive leadership, create a comfortable work environment, and motivate employees through regular training to improve employee performance on an ongoing basis.